Canopy garden model for synergy of land and sea area on Papan Island in Tojo Una Una Regency, Central Sulawesi - Bakri, Muhammad Bakri; Kasim, Anita Ahmad; Timbang, Gator (Applied Engineering and Technology, 2024)
Pulau Papan is one part of the Togean archipelago, Kabupaten Tojo Una Una. Initially, the Pulau Papan area was part of Tiga Pulau Village, Walea Islands District and Malenge Village, Talatako District, because the people who lived in this area came from these two villages. However, in 2011 Pulau Papan was expanded along with the increase in the number of family heads by 638 people and became part of the Kadoda Village area, Talatako District. The aim of this research is to build synergy in destination development between sea space and land/island space by creating regional nodes that are beautiful and function for the public. The public function that is formed can be utilized by the community both as a public space and a functional area that is beneficial for the residents of Pulau Papan, for example a green area containing vegetables for the residents. This vegetable green area is needed because of the limited vegetables on Pulau Papan. The solution proposed in this research is to design a canopy garden model that can become a green structure in the Pulau Papan area. The canopy garden will function to synergize the arrangement of land and sea areas on Pulau Papan. This canopy garden modeling was obtained through a survey process of the Pulau Papan area, then determining the meeting points for the mobility of residents on Pulau Pulau Papan. The public function that is formed can be utilized by the community both as a public space and a functional area that is beneficial for the residents ofÂ  Pulau Papan, for example a green area containing vegetables for the residents.